Relationship Between Anxiety Levels and Patient Adherence to Dental Treatment - Reca, Reca; Fadli, Fadli (Journal of Health Science and Medical Therapy, 2025)
Background and Objective: Patient compliance in undergoing dental treatment is a crucial factor for the success of therapy. However, it is often influenced by various factors, including psychological conditions such as anxiety levels. Therefore, this study aimed to determine whether there is a relationship between anxiety levels and patient compliance in receiving dental treatment at Cut Mutia General Hospital, North Aceh. Methods: This research employed a quantitative approach with a cross-sectional design. Data were collected using structured questionnaires distributed to outpatients in the dental care unit. The relationship between anxiety levels and patient compliance was analyzed using the Chi-Square statistical test. Results: The analysis revealed a statistically significant relationship between anxiety levels and patient compliance in undergoing dental treatment (Chi-Square value = 9.574; p = 0.008). Patients with mild anxiety exhibited a compliance rate of 64%, while those who felt calm showed the highest compliance rate at 84.6%. In contrast, patients with moderate anxiety demonstrated the lowest compliance rate at only 25%. These findings indicate that lower anxiety levels are associated with higher patient compliance in following dental treatment recommendations. Conclusion and Recommendation: The study concludes that there is a significant statistical relationship between anxiety levels and patient compliance in dental care at Cut Mutia General Hospital, North Aceh. Patients with lower anxiety tend to show higher compliance. It is recommended to implement psychological interventions, including educational approaches and empathetic communication, to reduce anxiety and enhance patient adherence to dental treatment procedures.